ROBOT MOBIL PENCARI TARGET DALAM MENGHINDARI RINTANGAN BERBASIS ARDUINO - sam, samuel julianda berkat waruwu; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2021)
Technology is a collection of hardware that is interconnected by using programming languages ​​so that they can work with each other in helping humans complete the most difficult, dangerous and repetitive tasks or jobs. This technology is like a mobile robot that helps detect the presence of a bomb, making it easier for humans to perform dangerous tasks. This final project aims to make a car robot consisting of a combination of hardware such as Arduino Mega 2560, DC motor 4 wide driver gear, IC L298N driver, HC-SR 4 sensor, push button, infrared flame detector sensor, and 16x2 LCD using language. Arduino sketch programming that has been compiled into the Arduino mega2560 board using ATMega 16U2, Arduino mega2560 has been equipped with an ATMega2560 microcontroller as a hardware control center for a car robot so that it can run automatically or without user control in search for targets in passing predetermined obstacles. The car robot will stop working when the target it is looking for has been found. Based on the results of research that has been carried out by researchers several times, the robot car designed by the researcher can move and operate according to the concept that has been set by the researcher.